PAGELARAN WAYANG DAN PENYEBARAN INFORMASI PUBLIK - Walujo, Kanti (P2KK LIPI, 2007)
Puppet shows (wayang) are usually used as a medium of communication, especially for disseminating of public information. Those messages could be disseminated through dialogue between heroes of puppets, or humors between clown services, or by the songs sing by the sindens (singers). Those wayang is not only performed in the stage but also in the mode of colaboration with the other modern mass media such as radio, television, film and internet. Keywords: wayang, dissemination, public information